STRATEGI PROMOSI DAN BRANDING MUSEUM LAYANG-LAYANG INDONESIA MELALUI PEMBUATAN VIDEO PROFIL - Wulan Purnama Sari; Claribel Halim; Tracy Zagitania3; Marcya Stevanni; Trisna Prasetya Hadinata; Jonathan Sim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
The development of information technology in the digital era has transformed the way people access information, including in the fields of promotion and cultural preservation. Museum Layang-Layang Indonesia (The Kites Museum of Indonesia), as one of Indonesia’s educational tourism destinations, holds great potential in introducing traditional cultural values but still faces challenges in terms of digital publication and promotion. This Community Service Program aims to assist The Kites Museum of Indonesia in strengthening its promotional and branding strategies through the production of an engaging, informative, and representative profile video. The implementation consisted of three stages: pre-production (coordination and field observation), production (video shooting, interviews, and documentation of museum activities), and post-production (editing, review, and video publication). The profile video was developed using the Multimedia Development Life Cycle (MDLC) approach, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The result is a profile video that visually and communicatively presents the museum’s identity, history, collections, and cultural values. The video serves as a digital promotional medium as well as an educational tool accessible through various online platforms. Through this activity, the museum gains an effective promotional medium to strengthen its image and attract public interest, while the community service team gains practical experience in applying digital communication. Overall, this program contributes to the promotion and preservation of traditional culture through creative and innovative approaches in the digital era. Perkembangan teknologi informasi di era digital telah mengubah cara masyarakat dalam mengakses informasi, termasuk dalam bidang promosi dan pelestarian budaya. Museum Layang-Layang Indonesia sebagai salah satu destinasi wisata edukatif memiliki potensi besar dalam memperkenalkan nilai budaya tradisional, namun masih menghadapi kendala dalam aspek publikasi dan promosi digital. Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk membantu Museum Layang-Layang Indonesia dalam memperkuat strategi promosi dan branding melalui pembuatan video profil yang menarik, informatif, dan representatif. Metode pelaksanaan kegiatan meliputi tiga tahapan, yaitu pra-pelaksanaan (koordinasi dan observasi lapangan), pelaksanaan (pengambilan gambar, wawancara, dan dokumentasi aktivitas museum), serta pasca pelaksanaan (proses penyuntingan, peninjauan, dan publikasi video). Pembuatan video profil dilakukan menggunakan pendekatan Multimedia Development Life Cycle (MDLC) yang mencakup tahapan concept, design, material collecting, assembly, testing, dan distribution. Hasil kegiatan berupa video profil yang menampilkan identitas, sejarah, koleksi, serta nilai budaya museum secara visual dan komunikatif. Video ini berfungsi sebagai media promosi digital sekaligus sarana edukatif yang dapat diakses melalui berbagai platform daring. Melalui kegiatan ini, museum memperoleh media promosi yang efektif untuk memperkuat citra dan menarik minat masyarakat, sementara tim pengabdian memperoleh pengalaman praktis dalam penerapan komunikasi digital. Secara keseluruhan, kegiatan PKM ini berkontribusi dalam memperkenalkan budaya tradisional melalui pendekatan kreatif dan inovatif di era digital.